Gland Preservation in Patients Undergoing Sialoendoscopy. (14th March 2017) - Achim, Virginie; Light, Tyler J.; Andersen, Peter E.
Abstract : Objective: Sialoendoscopy is a minimally invasive technique for the treatment of obstructive sialadenitis. We aim to describe treatment considerations and report our ultimate rate of gland preservation. Study Design: Case series with chart review. Setting: Academic tertiary hospital. Subject and Methods: A total of 128 consecutive sialoendoscopy cases for obstructive sialadenitis between 2009 and 2015 were evaluated. Procedures included endoscopic stricture dilation, basket‐assisted stone retrieval, Holmium laser lithotripsy, and combined endoscopic transoral stone excision. Resolution of symptoms, need for additional procedures, and rate of subsequent adenectomy were investigated. Results: Sialoendoscopy was completed in 120 of 128 patients (94%). There were 87 parotid gland cases and 41 submandibular gland cases. Endoscopic stricture dilation was attempted in 97 patients and successful in 99%. A sialolith was identified in 31 cases and removed by basket‐assisted stone retrieval (10 cases), Holmium:YAG laser stone fragmentation (10 cases), and combined endoscopic transoral stone extraction (4 cases). In 8 cases overall, sialoendoscopy failed, with immediate adenectomy. At a mean follow‐up of 18 months, 39 patients (33%) reported recurrence of symptoms, with 90% in the stricture group. For the entire cohort, gland preservation occurred in 112 of 128 patients (88%). Conclusions: Sialoendoscopy is an effective technique, with few patients requiring additional procedures. Newer interventional approaches allow for stone retrieval without adenectomy. Patients in the stricture group were more likely to have recurrent symptoms as compared with the sialolithiasis group but often benefit from additional sialoendoscopic procedures, leading to a high overall rate of long‐term gland preservation of 91%.